Nutrients Intake and Hypertension - Fantin, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Hypertension is a major health problem worldwide, increasing cardiovascular (CV) risk and mortality. Together with pharmacological treatments, non-pharmacological approaches, such as nutrient intake modifications, play an important role in optimizing treatment. A link has been demonstrated between hypertension and body weight as well as dietary habits. The aim of this Special Issue is to improve the understanding of the relationships between some nutrients and hypertension, and of the effects of different dietary approaches on hypertension regulation from different points of view.